The Effect Of Permissive Parenting on Adolescent Sexual Behavior Pasar 7 Beringin Tembung - Kesuma Dewi, Ira; Haryati, Endang (International Journal of Economics and Management, 2023)
The purpose of this study was to determine the effect of permissive parenting on premarital sexual behavior in adolescents. This research method uses quantitative methods. The population in this study amounted to 350 people and the sample in this study amounted to 65 people. The sampling technique in this study used a purposive sampling technique. The data collection method in this study used the permissive parenting scale and the premarital sexual behavior scale. The data analysis technique uses simple linear regression analysis. The significance value obtained is 0.054 > 0.05, which means The regression equation based on research data is not significant, meaning that the linear regression model does not meet the linearity criteria. While the coefficient of determination obtained is (R2) 0.057. This means that permissive parenting style influences premarital sexual behavior by 5.7%.